An Efficient Feature Selection Approach for Intrusion Detection System using Decision Tree - Das, Abhijit; -, Pramod; S, Sunitha B (International journal of advanced computer science & applications, 2022)
The intrusion detection system has been widely studied and deployed by researchers for providing better security to computer networks. The increasing volume of attacks, com-bined with the rapid improvement of machine learning (ML) has made the collaboration of intrusion detection techniques with machine learning and deep learnings are a popular subject and a feasible approach for cyber threat protection. Machine learning usually involves the training process using huge sample data. Since the huge input data may cause a negative effect on the training and detection performance of the machine learning model, feature selection becomes a crucial technique to rule out the irrelevant and redundant features from the dataset. This study applied a feature selection approach for intrusion detection that incorporated state-of-the-art feature selection algorithms with attack characteristic feature to produce an optimized set of features for the machine learning algorithms, which was then used to train the machine learning model. CSECIC- IDS2018 dataset, the most recent benchmark dataset with a wide attack diversity and features have been used to create the efficient feature subset. The result of the experiment was produced using machine learning models with a decision tree classifier and analyzed with respect to the accuracy, precision, recall, and f1 score.